2015
DOI: 10.1016/j.cam.2014.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Mixed finite element methods for two-body contact problems

Abstract: a b s t r a c tThis paper presents mixed finite element methods of higher-order for two-body contact problems of linear elasticity. The discretization is based on a mixed variational formulation proposed by Haslinger et al. which is extended to higher-order finite elements. The main focus is on the convergence of the scheme and on a priori estimates for the h-and the p-method. For this purpose, a discrete inf-sup condition is proven which guarantees the stability of the mixed method. Numerical results confirm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Following the work [9] we transfer the presented active-set strategies for Mortar methods to mixed finite elements, which were introduced by Haslinger [28] for low order. We generalize the solving methods to higher-order discretizations that are proposed in [29] and general friction laws depending on the contact forces.…”
Section: Semi-smooth Newton Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Following the work [9] we transfer the presented active-set strategies for Mortar methods to mixed finite elements, which were introduced by Haslinger [28] for low order. We generalize the solving methods to higher-order discretizations that are proposed in [29] and general friction laws depending on the contact forces.…”
Section: Semi-smooth Newton Methodsmentioning
confidence: 99%
“…However the splitting of the normal and tangential parts is clear. Stability of the described discretization is proven for the elastic case and balanced h, H, p, and q in [29]. It is shown that if the inequality…”
Section: Discretizationmentioning
confidence: 97%
See 3 more Smart Citations